The grand scheme of things : a novel - Jay, Warona (Washington Square Press / Atria, 2025)
"Meet Relebogile Naledi Mpho Moruakgomo. Or, for short, Eddie: an aspiring playwright who dreams of making it big in London's theater world. But after repeated rejections from white talent agents, Eddie suspects her non-white sounding name might be the problem. Enter Hugo Lawrence Smith: good looking, well-connected, charismatic and... very white. Stifled by his law degree and looking for a way out of the corporate world, he finds a kindred spirit in Eddie after a chance encounter at a cafe. Together they devise a plan, one which will see Eddie's play on stage and Hugo's name in lights. They send out her script under his name and vow to keep the play's origins a secret until it reaches critical levels of success. Then they can expose the theater world for its racism and hollow clout-chasing. But as their plan spins wildly out of control, Eddie and Hugo find themselves wondering if their reputations, and their friendship, can survive." --